2016
DOI: 10.1038/ncomms10895
|View full text |Cite
|
Sign up to set email alerts
|

The Gq signalling pathway inhibits brown and beige adipose tissue

Abstract: Brown adipose tissue (BAT) dissipates nutritional energy as heat via the uncoupling protein-1 (UCP1) and BAT activity correlates with leanness in human adults. Here we profile G protein-coupled receptors (GPCRs) in brown adipocytes to identify druggable regulators of BAT. Twenty-one per cent of the GPCRs link to the Gq family, and inhibition of Gq signalling enhances differentiation of human and murine brown adipocytes. In contrast, activation of Gq signalling abrogates brown adipogenesis. We further identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 46 publications
4
87
0
Order By: Relevance
“…ET‐1 increased IP 1 production, which was also attenuated by Ebselen pretreatment (Figure f). Interestingly, similar to FR (Klepac et al, ), Ebselen not only enhanced the differentiation of brown adipocytes but also rescued the ET‐1‐induced inhibition of brown adipogenesis as determined by Oil Red O staining of lipid droplets and expression of thermogenic (UCP‐1) and adipogenic markers (PPARγ; Figures g–j and S17).…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…ET‐1 increased IP 1 production, which was also attenuated by Ebselen pretreatment (Figure f). Interestingly, similar to FR (Klepac et al, ), Ebselen not only enhanced the differentiation of brown adipocytes but also rescued the ET‐1‐induced inhibition of brown adipogenesis as determined by Oil Red O staining of lipid droplets and expression of thermogenic (UCP‐1) and adipogenic markers (PPARγ; Figures g–j and S17).…”
Section: Resultsmentioning
confidence: 53%
“…Ebselen significantly reduced the CNO‐induced increase in IP 1 levels demonstrating its ability to inhibit G q signalling also in intact cells, albeit not as strongly as FR (Figure e). In addition, we studied the effect of Ebselen on endogenous G q activators using ET‐1, which we previously identified as an autocrine regulator of G q signalling in brown adipocytes (Klepac et al, ). ET‐1 increased IP 1 production, which was also attenuated by Ebselen pretreatment (Figure f).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These brite adipocytes also express the α 1A ‐ and α 1D ‐adrenoceptor, with acute activation of the α 1A ‐adrenoceptor in differentiated brite adipocytes increasing calcium mobilisation, glycolysis, and glucose uptake but having no effect on oxygen consumption (Merlin, Sato, Nowell, et al, ). One recent study (Klepac et al, ) suggested that activation of Gαq/11 coupled receptors (such as the endothelin ET A receptor) reduces brown and brite adipocyte differentiation and decreases UCP1 expression, suggesting that Gαq/11 receptor antagonists may be a promising target to increase browning. Hence, further studies aimed at investigating the acute and long‐term effects of Gαq/11 receptor activation or inhibition should be performed.…”
Section: Emerging Role Of Brite Adipocytesmentioning
confidence: 99%
“…47 ] i via Gq-coupled receptor activation (possibly the α1 adrenergic receptor) could be involved in the expression of UCP1 and whole-body energy expenditure of BAT and beige adipocytes. 52) In beige adipocytes, ATP-dependent Ca 2+ cycling by sarco/endoplasmic reticulum Ca 2+ -ATPase 2b (SERCA2b) and ryanodine receptor 2 can generate heat, which is independent of UCP1. 53) Membrane hyperpolarization by activation of a two-pore domain potassium channel (KCNK3) reduced Ca 2+ -influx and impaired adrenergic receptor-mediated thermogenesis in brown adipocytes.…”
Section: Mechanism Of Thermogenesis In Brown and Beigementioning
confidence: 99%